Apatites and their Synthetic Analogues Synthesis, Structure, Properties and Applications - Ptacek, Petr (IntechOpen, 2016)
Apatite-type minerals and their synthetic analogues are of interest of many industrial branches and scientific disciplines including material sciences, chemical industry, agriculture, geology, medicine and dentistry. This book provides a basic overview of general knowledges of this topic in order to provide the comprehensive survey from a scientific and technological perspective. The book is divided into 10 chapters, which are devoted to the structure and properties of minerals from the supergroup of apatite, experimental techniques of preparation and characterization of synthetic analogues of apatite minerals, substitution in the structure of apatite as well as utilization of these materials in wide range of common and special advanced applications in industry, material sciences and research. Additionally, the phosphate rocks, their classification, geological role, mining and beneficiation of phosphate ore, production of elemental phosphorus, phosphoric acid and fertilizers are also described. Although this book is meant for chemist, material scientist and research engineers, the individual chapters contain theoretical background, historical aspects as well as examples of synthetic and analytical methods which may be also interesting for students and non-expert readers as well.